Two-Component MprAB System Regulates the Expression of Genes Involved in Cell Envelope Biosynthesis in Corynebacterium glutamicum - Yu Zou; Danni Huang; Xiuxia Liu; Yankun Yang; Chunli Liu; Ye Li; Zhonghu Bai (Microorganisms)
To accurately detect internal and environmental cues, bacteria have evolved signal transduction pathways such as two-component systems (TCSs) to reprogram appropriate genetic and physiological functions for adaptation and survival. The MprAB TCS is commonly found in actinobacteria and has been associated with important processes such as mycobacterial virulence, nutrient starvation, and environmental stress, particularly cell envelope stress. However, a comprehensive investigation of the function and response network of the MprAB TCS in corynebacteria remains to be carried out. In this study, we report that the MprAB TCS (previously named CgtSR2) plays a critical role in regulating genes involved in cell envelope remodeling in C. glutamicum. The results indicated that the MprAB TCS directly controls a broad regulon, including cell wall biosynthesis proteins, alternative sigma factors, secreted proteins of unknown function, and the mprAB gene locus itself. Among these, the HtrA-like serine protease confers vancomycin and penicillin resistance. Furthermore, we found that the function of the cell envelope was disrupted during overexpression of mprA, resulting in elongated cell morphology and increased cell membrane permeability, as well as enhanced excretion of L-alanine. In conclusion, our findings provide novel insights into how the conserved MprAB TCS controls cell envelope homeostasis in distant actinobacteria.